Heat Transfer Equations Development of Cooling Water Droplet Direct Contact Condensation With Steam Containing Non Condensable Gas (NCG) - Armeza Dani - Nim: 13113127 , Anton
Indonesia has a huge geothermal resource potential of 28.9 GWe, which can be converted into electrical energy to meet the needs of the community through geothermal power plant. Any steam taken from geothermal wells has non-condensable gas content, thereby reducing the efficiency of geothermal energy utilization. Allegedly, the non-condensable gas will block the heat transfer inside the condenser. The condenser used in geothermal power plant is a spray tipe direct contact condenser. The cooling water flowing into the condenser will atomized into small drop by spray nozzle. The vapor that enters with the non-condensable gas will transfer its heat to the cooling water droplet. The heat transfer mechanism needs to be analyzed to determine the phenomenon. In this bachelor thesis, a direct condensation heat transfer model is proposed between the condensed vapor and the liquid grains covered with NCG. The influential parameters are then identified and grouped in dimensionless parameters by the Buckingham Pi method. The dimensionless numbers generated include Nu, Re, Ja, Wnc, dl/Dnc, and Prnc. Then the experimental data from spray condenser experiment by Kulic [15], Ranggana [16], and Bontozoglou [17] were processed and developed into a heat transfer correlation equation.